Comprehensive DNA microarray expression profiles of tumors in tenascin-C-knockout mice. Issue 10 (3rd October 2017) - Matsumoto, Kaori; Nakai, Yuji; Hoshino, Masaru; Yamazaki, Koki; Takioto, Yoshiaki; Takadera, Satoru; Nakagawa, Takayuki; Nishimura, Ryohei; Kusakabe, Moriaki
Abstract: Tenascin-C (TNC), an extracellular matrix glycoprotein, plays a pivotal role in tumor growth. However, the mechanism whereby TNC affects tumor biology remains unclear. To investigate the exact role of TNC in primary tumor growth, a mouse mammary tumor cell line, GLMT1, was first developed. Subsequently, global gene expression in GLMT1-derived tumors was compared between wild-type (WT) and TNC-knockout (TNKO) mice. Tumors in WT mice were significantly larger than those in TNKO mice. DNA microarray analysis revealed 447 up and 667 downregulated in the tumors inoculated into TNKO mice as compared to tumors in WT mice. Validation by quantitative gene expression analysis showed that Tnc, Cxcl1, Cxcl2, and Cxcr2 were significantly upregulated in WT mice. We hypothesize that TNC stimulates the CXCL1/2-CXCR2 pathway involved in cancer cell proliferation. Abstract: : The extracellular matrix glycoprotein tenascin-C stimulates the CXCL1/2-CXCR2 pathway involved in cancer cell proliferation and suppresses pro-inflammatory cytokines.